A Novel Synthesis of Green Apatite‐Type Y5(SiO4)3N:Eu2+ Phosphor via SiC‐Assisted Sol–Gel Route. Issue 3 (10th January 2016) - Wan, Jieqiong; Liu, Qian; Liu, Guanghui; Zhou, Zhenzhen; Ni, Jia; Xie, Rong‐jun
Abstract : A green Y5 (SiO4 )3 N:Eu 2+ phosphor has been successfully prepared by developing a new SiC reduction‐assisted sol–gel method. The valence state of Eu ions was identified with XPS analysis and the photoluminescence spectrum presents a Eu 2+ typical broad green emission band. XRD analysis, photoluminescence and excitation measurement, and FTIR test were also carried out, to obtain crystal phase, light emitting, and chemical bonding results. The specific mechanism of SiC reductant in the synthetic process was studied in details. This novel method shows lower equipment requirements and is cost saving. The method can extend applications in synthesizing other silicon‐based oxynitrides.